Introduction: Digital History in African Studies. - Hart, Jennifer (History in Africa: A Journal of Method, 2020)
This brief introduction to a special section on Digital History in African Studies situates three articles on recent digital humanities initiatives among African historians within the broader histories of the use of digital methodologies in the study of Africa. In particular, it highlights the way that Africanist digital scholarship sits at the intersection of digital historical representation, community engagement, and academic research. While Africanist digital history builds on the work of a much broader digital humanities community, historians of Africa also draw on their discipline's long history of methodological innovation to raise important questions about the potential contributions and limitations of digital technologies in academic research.